Comparison of marine debris data collected by researchers and citizen scientists: Is citizen science data worth the effort?. (April 2017) - van der Velde, Tonya; Milton, David A.; Lawson, T.J.; Wilcox, Chris; Lansdell, Matt; Davis, Geraldine; Perkins, Genevieve; Hardesty, Britta Denise
Abstract: As part of a national research program studying the sources, distribution, and effects of litter entering the ocean, we established a national citizen science program engaging nearly 7000 primary and secondary students, teachers and corporate participants in collecting marine debris data around Australia's coastline. Citizen scientists undertook a one-day training program, which addressed data collection skills and academic topics in the national science curriculum. A subset of teachers and corporate sponsor staff participated in an intensive multi-day training program with researchers before venturing into the field. Data collected by citizen scientists were compared with data collected by researchers at nearby locations. We found the citizen science data were of equivalent quality to those collected by researchers, but there were differences among students. Primary school students detected more debris than did older secondary students. Students detected small items (< 1 cm 2 ), and were as accurate as researchers in identifying debris type and size categories. However, sampling approach was important — students detected more debris during quadrat searches than during strip transects. Comparing researcher effort to volunteer-collected data, citizen scientists were often more efficient (per m 2 ) than researchers at collecting marine debris, but the results varied among methods. Researchers made more surveys within a given day (0.8 surveys/person-day). However, participants of one day programs working with secondary students or adults were nearly as efficient (0.6 surveys/person-day). This study shows that engaging with citizen scientists can broaden the coverage and increase the sampling power of coastal litter and other ecological survey assessments without compromising the data. Highlights: With appropriate training, citizen scientist collected data are robust and reliable. Primary school student participants found more litter on beaches than did older students. Citizen scientists were at least as efficient as researchers in undertaking marine debris sampling. Intensive, multi-day training did not provide a detectable increase in data quality.